INTERMEDIAL INDIAN OCEAN - In Conversation with Mshai Mwangola (Workshop Intermedial Indian Ocean - 2021, 2023)
As part of the Indian Ocean events in November 2021, Dr. Mshai Mwangola, Ph.D., was a guest of the Africa Multiple Cluster of Excellence in Bayreuth. In this interview, she talks with Clarissa Vierke, Professor of Literatures in African Languages at the @unibayreuth, about her performance lecture and her kanga workshop. Mshai holds a PhD in Performance Studies from Northwestern University (USA). Her thesis on Kenya’s “Uhuru Generation”, titled ‘Performing Our Stories, Performing OurSelves’, approaches the idea of a generational historical mission through the re-creation, invocation and facilitation of performance as a site of individual and communal reflection. Mshaï's pedagogy, research and creative work is grounded in understanding performance as both the process and product of meaning-making. In her performance lecture for the Intermedial Indian Ocean Event entitled "Hadithi Njoo: Leso as Palimpseston" she talked about the history of the evolution of leso as well as some of the social, cultural and political uses of this textile.